Strategic plan for Davao Doctors Cooperative - Ruiz, Jan Rhea B. (School of Management, University of the Philippines Mindanao, 2012)
Cooperatives are known to be great mobilizers of savings. It serves as a venue for pooling of resources to finance the creation of more assets and promote entrepreneurship. Davao Doctors Cooperative is an organization duly registered with the Cooperative Development Authority, established in 1988. Its primary purpose is to generate funds and extend credit to members for productive and providential purposes to help them improve their socio-economic condition. Like any other cooperatives, DDCoop is also facing problems such as low rate of membership and collection of receivables. As an employee cooperative, DDCoop membership comprised only of 25% coming from the hospital. With regards to its receivables, the cooperative is not efficient in credit collection. It still has an outstanding balance of P40 million loans receivables which is equal to 46% of its total amount released. This paper attempts to identify critical factors that hinder DDCoop from solving these problems. The conceptual framework of Mazzarol (2012) was adapted. SWOT analysis was used in formulating strategic options. As to the evaluation and assessment, KRA (Key Results Area) will be used as a tool.